1997
DOI: 10.1007/s001250050721
|View full text |Cite
|
Sign up to set email alerts
|

Reversibility of insulin resistance in obese diabetic patients: role of plasma lipids

Abstract: It has been shown in a large sample of the general population, that obesity itself represents an independent risk factor for increased mortality [1,2].Therefore, obesity and its related disorders constitute one of the most relevant health and social problems of the present era because of the high cost and disability which it imposes on the individual and the community [3][4][5].Insulin resistance is a prominent biological marker of obesity. In particular, it is a phenomenon represented by high plasma insulin l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
93
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 120 publications
(102 citation statements)
references
References 41 publications
8
93
1
Order By: Relevance
“…Glucose tolerance and insulin sensitivity were significantly heightened post-surgery, even in patients who were NGT at baseline. Previous studies [4][5][6][7] have shown that bariatric surgery is extremely effective in improving glucose tolerance, insulin sensitivity and, to some extent, insulin secretion (as inferred from homeostasis model assessment estimates or the acute insulin response to i.v. glucose).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Glucose tolerance and insulin sensitivity were significantly heightened post-surgery, even in patients who were NGT at baseline. Previous studies [4][5][6][7] have shown that bariatric surgery is extremely effective in improving glucose tolerance, insulin sensitivity and, to some extent, insulin secretion (as inferred from homeostasis model assessment estimates or the acute insulin response to i.v. glucose).…”
Section: Discussionmentioning
confidence: 99%
“…In morbidly obese patients undergoing bariatric surgery, one factor contributing to the restoration of normal glucose tolerance is the surgery-induced increase in insulin sensitivity [4][5][6][7]. Although some data are available [5,[7][8][9], the role of beta cell function, its relationship with insulin sensitivity, and the contribution of either factor to the improvement in glucose tolerance are not clearly established.…”
mentioning
confidence: 99%
“…We have previously demonstrated that insulin resistance and type 2 diabetes are reversible after malabsorptive bariatric surgery [16][17][18]. However, we are far from understanding the mechanisms involved.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the skeletal muscle, which represents the principal site of insulin-mediated glucose disposal, 4 shows an increased content of triglycerides in obesity. 5,6 In turn, both circulating 7 and muscle levels of triglycerides are strictly related to the whole body glucose uptake in an inverse fashion. 8 Furthermore, a marked lowering of plasma TG brough about by bariatric surgery (ie bilio-pancreatic diversion, BPD), which in all likelihood reflects the decrease of tissue TG levels, led to the reversibility of diabetes mellitus in two normal-weight young sisters with a genetic defect of lipoprotein lipase (LPL) activity and with ensuing chylomicronemia.…”
Section: Introductionmentioning
confidence: 99%